2015
DOI: 10.3762/bjnano.6.44
|View full text |Cite
|
Sign up to set email alerts
|

In situ scanning tunneling microscopy study of Ca-modified rutile TiO2(110) in bulk water

Abstract: SummaryDespite the rising technological interest in the use of calcium-modified TiO2 surfaces in biomedical implants, the Ca/TiO2 interface has not been studied in an aqueous environment. This investigation is the first report on the use of in situ scanning tunneling microscopy (STM) to study calcium-modified rutile TiO2(110) surfaces immersed in high purity water. The TiO2 surface was prepared under ultrahigh vacuum (UHV) with repeated sputtering/annealing cycles. Low energy electron diffraction (LEED) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…When the thickness exceeds 3 nm (part II), apparently, the resistances surge sharply. As an intensively studied insulator (bandgap ~ 3.5 eV), it is suggested that the electron tunneling distance of TiO 2 is about several nanometers [57], and electron conductivity may degrade rapidly when TiO 2 thickness is above this value. In this case, the 3 nm is probably the tunneling distance for the poorly crystallized TiO 2 , which explains the much declined capacity when its thickness exceeds 3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…When the thickness exceeds 3 nm (part II), apparently, the resistances surge sharply. As an intensively studied insulator (bandgap ~ 3.5 eV), it is suggested that the electron tunneling distance of TiO 2 is about several nanometers [57], and electron conductivity may degrade rapidly when TiO 2 thickness is above this value. In this case, the 3 nm is probably the tunneling distance for the poorly crystallized TiO 2 , which explains the much declined capacity when its thickness exceeds 3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, systems that expose a surface with pronounced anionic character to the electrolyte represent a clear majority in EC-STM; the opposite is encountered more seldom. , The emerging field of electrochemical surface science of oxides , and other highly adsorptive materials such as hexagonal boron nitride, however, may change this ratio very soon. If present, the anionic character of a substrate renders it immune toward adsorption of also negatively charged tungstates, which form under all but the most acidic pH conditions ( vide supra ), and explains its conspicuous absence in the EC-STM literature.…”
Section: Discussionmentioning
confidence: 99%
“…The second one, with a lower intensity, was located at lower binding energies of 459.35 eV and 463.32 eV, probably associated with TiO 2 . 36,37 The peaks of O 1s were located at 531.07 eV and 533.12 eV. The O 1s in TiO 2 showed a higher binding energy, while the O 1s had a lower binding energy in PO 4…”
Section: Biomaterials Science Papermentioning
confidence: 96%